Reassessing the indicator value of the EPT group in karst rivers under hydromorphological pressure - Marina Šumanović; Ivana Pozojevic; Marina Vilenica; Renata Matoničkin Kepčija; Zlatko Mihaljević; Vesna Gulin Beljak; Marko Miliša (Water Supply, 2024)
Hydromorphological degradation is one of the most common stressors to freshwater ecosystems nowadays. Rivers lose riparian vegetation, habitat heterogeneity, natural flow velocity, etc., due to hydromorphological alterations. We analyzed macroinvertebrate communities in a wide range of hydromorphological conditions – from near natural sites to significantly altered water bodies, focusing on Ephemeroptera, Plecoptera, and Trichoptera (EPT). Considering that the EPT group is a quite sensitive and generally stenovalent group, we wanted to examine which of the hydromorphological pressures affects them the most. We also wanted to identify indicator taxa for different levels of degradation: minor, moderate, and severe. We collected samples from 84 karst rivers sites in Croatia. We found 52 taxa of EPT (Ephemeroptera – 21, Plecoptera – 11, Trichoptera – 20). Changes in river morphology proved to be the most important stressor affecting the distribution of the EPT group. Hydrological regulation did not show significance toward the EPT community, possibly due to the karst nature of the rivers studied. The most sensitive EPT taxa were those with the greatest preference for macrophytes and lithal habitats. More tolerant EPT taxa were those with a wide range of habitat preferences and/or taxa that feed on particulate organic matter. HIGHLIGHTS Our research underscores the pivotal role of morphological changes in rivers as the primary stressor impacting EPT communities.; We identify indicator taxa for different levels of hydromorphological degradation.; Focusing on the understudied karst rivers, our research provides unique insights into the complex and heterogeneous habitats of these ecosystems.; Reliable metrics for assessing river health.;